2022
DOI: 10.1155/2022/9914173
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Various Types of Berries Extract for the Synthesis of ZnO Nanocomposites and Exploring Their Antimicrobial Potential for Use in Herbal Medicines

Abstract: Nanoscience has developed various greener approaches as an alternate method for the synthesis of nanoparticles and nanocomposites. The present study discusses the efficacy of berries extract for the synthesis of ZnO nanocomposites. Characterization of synthesized nanocomposite were done by SEM, UV/VIS spectrophotometry, Fourier transform infrared (FTIR) spectroscopy, and XRD techniques. The crystalline nature of the synthesized nanoparticles was verified by XRD pattern in the range of 10-80 nm. The UV absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…If achievement is important to the learners, it is also important to society, as the progress of society depends primarily on the quality of the learners according to their upbringing, the type of learning they receive, and what they have achieved goals. (Dar et al, 2022)…”
Section: Achievementmentioning
confidence: 99%
“…If achievement is important to the learners, it is also important to society, as the progress of society depends primarily on the quality of the learners according to their upbringing, the type of learning they receive, and what they have achieved goals. (Dar et al, 2022)…”
Section: Achievementmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%